MULTIPLE GABBRO-GRANITE INTRUSIVE SERIES OF THE SYROSTAN PLUTON, SOUTHERN URALS: GEOCHEMISTRY AND PETROLOGY - Popov V.S.; Nikiforova N.F.; Bogatov V.I.; Lyapunov S.M.; Tikhomirov P.L. (My University, 2001)
The Syrostan gabbro-granite pluton is situated immediately to the west of the Main Uralian Fault and exemplifies a multiple series of five intrusive rhythms. Each rhythm characterizes a separate episode of emplacement of basic and acid magmas, which ascended from mantle and crustal sources contemporaneously, partly mixed with each other, and solidified in a sequence from basic to acid rocks according to decreasing solidus temperature. This model is confirmed by geochemical data demonstrating the specific fractionation trends for basic and acid magmas and the field of intermediate compositions typical of hybrid rocks. Experimental data on late-magmatic epidote stability and the plagioclase-amphibole thermobarometer were used to estimate the PT conditions of magma crystallization. The results obtained indicate the decrease in depth of magma solidification from early to late intrusive rhythms due to the rise of the magmatic column and the rapid denudation of the overlying rocks.
Keywords: Urals; Syrostan gabbro-granite pluton; Geochemistry; Petrology